INTERPRETATION OF THE MEANING OF KELONG-KELONG BOSI LOMPO (ᨅᨚᨔᨗ ᨒᨚᨄᨚ) HERMENEUTIC APPROACH: INTERPRETASI MAKNA KELONG-KELONG BOSI LOMPO (ᨅᨚᨔᨗ ᨒᨚᨄᨚ) PENDEKATAN HERMENEUTIKA - Asmi Arsyad; Djohar Amir; Syamsudduha Syamsudduha (Jurnal Kata, 2022)
This writing is intended to discuss meaning of song Bosi Lompo (ᨅᨚᨔᨗ ᨒᨚᨄᨚ)  using hermeneutic aproach. This research applies descriptive qualitative method by collecting data using inventory technique, reading observation, and taking a note. The technique analysis is identification, classification, analysis and description. Meaning analysis of the song with hermeneutic approach is conducted in some stages: analysis history of the song, analysis word in the lyric, analysis lyric in the distich, analysis distich in the song and analysis of the song with whole. The result of the research shows that the meaning of Bosi Lompo (ᨅᨚᨔᨗ ᨒᨚᨄᨚ) is prayer and the hope of farmer children for the rain that can make their parents plants grow well.